Geografia nos anos iniciais da educação básica: um estudo a partir de mapas da África elaborados por docentes - Silva, Marcos Aurélio Soares da (2021)
The study of Afrodescendant and indigenous history and culture is mandatory in all Brazilian public and private educational institutions. The research reported in this article sought to explore the ways in which six primary school teachers graphically represented Africa. As a theoretical support, the study was based on references from the movement to renew geography (SANTOS, 1994; 2004; VESENTINI, 2001; 2002), school geography (CALLAI, 2010; CAVALCANTI, 2000; 2002; 2012), as well as on the social subjectivity of teachers (JODELET, 2017; NOVAES, 2013; 2015; 2020; SERPA, 2019). Participants were invited to freely draw up a map of Africa using the Canvas application, and to answer a questionnaire using Google forms. The information produced was systematised and analysed in the light of critical geography and showed mute maps with little information on the continent, the object of the draws. This lack of information on Africa points to the need for greater investment in teacher training in the early years of primary education.